2010
DOI: 10.1007/s11069-010-9618-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential source zones for Himalayan earthquakes: constraints from spatial–temporal clusters

Abstract: The Himalayan fold-thrust belt has been visited by many disastrous earthquakes (magnitude [ 6) time and again. This active collisional orogen bordering Indian subcontinent in the north remains a potential seismic threat of similar magnitude in the adjoining countries like India, Pakistan, Nepal, Bhutan and China. Though earthquake forecasting is riddled with all conjectures and still not a proven presumption, identifying likely source zones of such disastrous earthquakes would be an important contribution to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…But these hypotheses need to be backed by experimental data. These inferences hold good for clustering of earthquakes in the Himalaya, especially in the lesser Himalaya where a characteristic earthquake model is apparent [10].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…But these hypotheses need to be backed by experimental data. These inferences hold good for clustering of earthquakes in the Himalaya, especially in the lesser Himalaya where a characteristic earthquake model is apparent [10].…”
Section: Discussionmentioning
confidence: 66%
“…in the frontal belt of Himalaya. Though Lesser Himalayan earthquakes and related seismic hazards have been studied in details [10], the seismogenesis due to MCT and clustering of earthquakes related to this are somewhat neglected or oversimplified. At the same time, the seismic potentiality of the MCT to generate moderate size events (1980( Gangtok, 1991 Uttarkashi, 1999 Chamoli, 2009 Bomdila etc.)…”
Section: Introductionmentioning
confidence: 99%
“…contained seismically monitored earthquake data recorded during the years 1900 -2010 by various agencies of the entire South Asia, which are statistically analyzed in this study to understand the nature and extent of seismogenesis in the Himalayan basin. We have correlated our results with other available published inferences to understand the nature of earthquake swarms and clusters [47]. In Figure 2, we attempted to show the completeness of the earthquake data which has been used in this study.…”
Section: Introductionmentioning
confidence: 82%
“…Compared to the regions already discussed, seismicity was found to be sparse in three regions, viz., south of the MBT, along the Jhelum Fault, and in the region along ISZ, roughly defined between MCT, Shyok Suture, Kishtwar Fault and Tso Morari Fault. Mukhopadhyay et al (2011) observed five spatial clusters in the vicinity of MCT in the entire Himalayan arc, and put forward the hypothesis that MCT is seismically active in segments. This aspect was used for segmentation of MCT (Mridula et al 2016, communicated).…”
Section: Tectonics Of the Regionmentioning
confidence: 95%